Probleemoplossing as taak van die departementshoof - Ferreira, Andre Michiel (2014)
M.Ed. (Educational Management) === Significant long term planning and the reaching of goals cannot be reached efficiently if they are constantly hampered by nonproductive problems. Therefore, effective problem solving and effective prevention are of cardinal importance in the multi-type workload of the head of department. The principal is the keyfigure in the school. In this respect, the principal should be supported by a management team, utilizing all facets of management in the school, including problem solving. Problem solving js a comprehensive task and one person alone does not have all the time or skills to run the school single-handedly. The head of department is the senior manager of his department and has a prime resposibility towards the effective functioning of his department. This implies that the head of department not only needs to be an educational leader, but he must also have the necessary managerial skills to be successful. During problem solving a certain thought-pattern of modusoperandi should be acquired. The way a head of department solves problems is an indication of his value as educational leader, and it follows that his skills at problem solving and effective behaviour will determine his success as an educational leader. This study will focus mainly on four basic management tasks: planning, organization, guidance and control.